Assessing mathematical thinking of primary school students - Mohd Nor, N.; Idris, N. (2008)
The recently reviewed primary school mathematics curriculum in Malaysia expects students to be provided with opportunities to develop their mathematical thinking. The traditional paper-and-pencil achievement tests normally given to students' are insufficient for assessing the true picture of the students' mathematical thinking. To assess students' mathematical thinking, teachers need to use assessment techniques that will collect evidence about the students' mathematical thinking process. This paper presents the result of an assessment of students' mathematical thinking through an item consisting of open ended tasks. The tasks will involve students checking for possibility of more than one solution to a problem.